Implications of Chitin Attachment for the Environmental Persistence and Clinical Nature of the Human Pathogen Vibrio vulnificus - Williams, Tiffany C. (American Society for Microbiology, 2014)
Vibrio vulnificus naturally inhabits a variety of aquatic organisms, including oysters, and is the leading cause of seafood-related death in the United States. Strains of this bacterium are genetically classified into environmental (E) and clinical (C) genotypes, which correlate with source of isolation. E-genotype strains integrate into marine aggregates more efficiently than do C-genotype strains, leading to a greater uptake of strains of this genotype by oysters feeding on these aggregates. The causes of this increased integration of E-type strains into marine “snow” have not been demonstrated. Here, we further investigate the physiological and genetic causalities for this genotypic heterogeneity by examining the ability of strains of each genotype to attach to chitin, a major constituent of marine snow. We found that E-genotype strains attach to chitin with significantly greater efficiency than do C-genotype strains when incubated at 20°C. Type IV pili were implicated in chitin adherence, and even in the absence of chitin, the expression level of type IV pilin genes (pilA, pilD, and mshA) was found to be inherently higher by E genotypes than by C genotypes. In contrast, the level of expression of N-acetylglucosamine binding protein A (gbpA) was significantly higher in C-genotype strains. Interestingly, incubation at a clinically relevant temperature (37°C) resulted in a significant increase in C-genotype attachment to chitin, which subsequently provided a protective effect against exposure to acid or bile, thus offering a clue into their increased incidence in human infections. This study suggests that C- and E-genotype strains have intrinsically divergent physiological programs, which may help explain the observed differences in the ecology and pathogenic potential between these two genotypes.